ENGINEERING OF ACOUSTIC TECHNOLOGY FOR UNDERWATER POSITIONING OBJECT - Billi Rifa Kusumah; Indra Jaya; Henry M. Manik; . Susilohadi (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2018)
Underwater Positioning System (UPS) is a system to track the existence of the position of an object by utilizing the arrival time of the signal measurement. On land, the system uses an electromagnetic signal called GPS. However, because it cannot penetrate water effectively, an acoustic signal is used as an alternative. The purpose of this research is to engineer the control system of data acquisition and underwater acoustic device to measure arrival time (TOA) and apply equation model for underwater sound source positioning system. the effective frequency resonance of the transducer and the hydrophone is at a frequency of 6 kHz. The acquisition control device is able to measure the TOA signal with an error on a digital channel smaller than an analog channel. The difference between the TOA values measured by oscilloscope and acquisition control system is caused by inaccuracy of threshold estimates at the receiver's peak detector circuit. The position of the sound source coordinates obtained from the equation model shows the highest difference in depth point (z) compared to points (x) and (y), caused by the equation model used is limited to four hydrophone units forming a horizontal baseline.